2019
DOI: 10.1080/00958972.2019.1595605
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ligand derivatization on the electronic properties of polyoxovanadate-alkoxide clusters

Abstract: Polyoxovanadate-alkoxide (POV-alkoxide) clusters are promising charge-carrier candidates for non-aqueous redox flow batteries (NRFBs), due in part to their easily-modified bridging alkoxide ligands. Herein, we report a series of new POV-alkoxide clusters featuring polar functional groups bound to the tertiary carbon of a tripodal, tris(hydroxymethyl)methane ligand (TRIS R ; R¼ C 2 H 5 , NO 2 , NMe 3 þ , NC 5 H 4 (Py), PyMe þ). These clusters were synthesized to better understand the role that peripheral ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Notably, these modications do not signicantly impact the electronics of the cluster core. [41][42][43] CV experiments were conducted with each cluster dissolved in MeCN in the presence of 100 mM MOTf (M ¼ [ n Bu 4 N] + , K + , Na + , Li + ) as the supporting electrolyte (Fig. 3, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these modications do not signicantly impact the electronics of the cluster core. [41][42][43] CV experiments were conducted with each cluster dissolved in MeCN in the presence of 100 mM MOTf (M ¼ [ n Bu 4 N] + , K + , Na + , Li + ) as the supporting electrolyte (Fig. 3, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…11b, R=CH 3 ). 130,131 Discussion of the effects of incorporation of tridentate ligands at the surface of POV-alkoxide clusters on cluster solubility and electronics is presented in a following section.…”
Section: Pov-alkoxides With Mixed-denticity Pendant Ligands As Buildimentioning
confidence: 99%
“…12). 126 Likewise, the incorporation of aliphatic, 130 pyridyl and amino 131 functionalized TRIS ligands onto the POV-ethoxide scaffold was accomplished; however, only moderate improvements to cluster solubility was observed. Polyether-backed tripodal ligands vastly improved the solubility of this system, inspiring researchers to directly incorporate ether alcohols into the cluster framework and yielding V 6 O 7 (OR) 12 (R = C 2 H 4 OCH 3 , C 2 H 4 OC 2 H 5 ).…”
Section: Physical Properties Of Pov-alkoxide Clustersmentioning
confidence: 99%
“…These observations are in accordance with the initial findings of Zubieta and coworkers, describing the fact that the electronic structure of [V 6 O 13 (TRIOL R ) 2 ] 2− is highly sensitive to the character of the "R" substituent on the tris(hydroxymethyl) methane ligand. 13 In stark contrast, our research group previously reported the synthesis and electrochemical characterisation of a family of tris(hydroxymethyl)methane substituted POV-alkoxide clusters [V 6 O 7 (OEt) 9 (TRIOL R )]; in examining the redox profiles of complexes [V 6 O 7 (OEt) 9 (TRIOL Et )] n and [V 6 O 7 (OEt) 9 (TRIOL NO2 )] n , the peripheral functional group modulates the potential of redox events of the cluster core by only −0.10 V. 37 Broadly speaking, the redox profile of the cluster core bearing twelve alkoxide functionalities appears relatively impervious to the electron donating or electron withdrawing properties of the "R" substituent of the tris(hydroxymethyl)methane ligand. We attribute this property to a relative decoupling of the electronic structure of the cluster core to its peripheral ligands.…”
Section: Electrochemical Consequences Of Surface Functionalisationmentioning
confidence: 99%
“…13 However, recent work from our research group has shown that the incorporation of similar functional groups at the surface of Lindqvist-type POV-alkoxide clusters fully saturated with bridging alkoxide ligands has a limited influence on the electrochemical profile of the assembly. 37 This result is surprising, given the similar structure of the vanadium oxide core of the two classes of cluster complexes. Nominally, these assemblies differ only by the number of bridging alkoxide ligands substituted at their surfaces.…”
Section: Introductionmentioning
confidence: 99%